Environmental isotopic and hydrochemical characteristics of groundwater systems in Daying and Qicun geothermal fields, Xinzhou Basin, Shanxi, China - Han, Dongmei; Liang, Xing; Currell, Matthew J; Song, Xianfang; Chen, Zongyu; Jin, Menggui; Liu, Changming; Han, Ying (Hydrological processes, 2010)
The conceptual hydrogeological model of the low to medium temperature Daying and Qicun geothermal fields has been proposed, based on hydrochemical characteristics and isotopic compositions. The two geothermal fields are located in the Xinzhou basin of Shanxi, China and exhibit similarities in their broad-scale flow patterns. Geothermal water is derived from the regional groundwater flow system of the basin and is characterized by Cl·SO₄-Na type. Thermal water is hydrochemically distinct from cold groundwater having higher total dissolved solids (TDS) (>0·8 g/l) and Sr contents, but relatively low Ca, Mg and HCO₃ contents. Most shallow groundwater belongs to local flow systems which are subject to evaporation and mixing with irrigation returns. The groundwater residence times estimated by tritium and ¹⁴C activities indicate that deep non-thermal groundwater (130-160 m) in the Daying region range from modern (post-1950s) in the piedmont area to more than 9·4 ka BP (Before Present) in the downriver area and imply that this water belong to an intermediate flow system. Thermal water in the two geothermal fields contains no detectable active ¹⁴C, indicating long residence times (>50 ka), consistent with this water being part of a large regional flow system. The mean recharge elevation estimated by using the obtained relationship Altitude (m) = - 23·8 x δ²H ([per thousand] ) - 121·3, is 1980 and 1880 m for the Daying and Qicun geothermal fields, respectively. The annual infiltration rates in the Daying and Qicun geothermal fields can be estimated to be 9029 x 10³ and 4107 x 10³ m³/a, respectively. The variable ⁸⁶Sr/⁸⁷Sr values in the thermal and non-thermal groundwater in the two fields reflect different lithologies encountered along the flow path(s) and possibly different extents of water-rock interaction. Based on the analysis of groundwater flow systems in the two geothermal fields, hydrogeochemical inverse modelling was performed to indicate the possible water-rock interaction processes that occur under different scenarios. Copyright © 2010 John Wiley & Sons, Ltd.